2011
DOI: 10.1007/s11259-011-9476-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of GDF9 gene and its association with litter size in goats

Abstract: Growth differentiation factor 9 (GDF9) was studied as a candidate gene for high prolificacy in goats. The polymorphism of exon 1 and flanking of GDF9 gene was detected by PCR-SSCP in five goat breeds with different prolificacy. Three genotypes (AA, AB and BB) were detected in goat breeds joined and two silent mutations (c.183A>C and c.336C>T) were identified in comparison genotype AA with genotype BB. Heterozygous genotype AB and wild type BB were detected in all five goat breeds and homozygous genotype AA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…These findings are in general agreement with the previous reports on does (Constantinou, 1989; Mellado et al, 1991; Amoah et al, 1996) and ewes (Laster et al, 1972; Smith, 1985; Gaskins et al, 2005). Though some genes have been identified for influencing litter size in goats (An et al, 2009; Chu et al, 2011; Feng et al, 2011), certain body weight along with desirable body condition at certain age and parity may be necessary for optimum metabolic requirements which in turn influence hypophyseal-pituitary-gonadal axis for more ovulation that ultimately determine the number of successful fertilization and subsequently litter size (Perry et al, 1991; Tummaruk et al, 2007). In earlier studies, body condition score, higher live weight, age, physical strength and less slopped rump angles were found to be associated with an increase possibility of multiple births in does (Constantinou, 1989; Mellado et al, 2008) and in ewes (Hall et al, 1994; Gonzalez et al, 1997; Gaskins et al, 2005; Aliyari et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in general agreement with the previous reports on does (Constantinou, 1989; Mellado et al, 1991; Amoah et al, 1996) and ewes (Laster et al, 1972; Smith, 1985; Gaskins et al, 2005). Though some genes have been identified for influencing litter size in goats (An et al, 2009; Chu et al, 2011; Feng et al, 2011), certain body weight along with desirable body condition at certain age and parity may be necessary for optimum metabolic requirements which in turn influence hypophyseal-pituitary-gonadal axis for more ovulation that ultimately determine the number of successful fertilization and subsequently litter size (Perry et al, 1991; Tummaruk et al, 2007). In earlier studies, body condition score, higher live weight, age, physical strength and less slopped rump angles were found to be associated with an increase possibility of multiple births in does (Constantinou, 1989; Mellado et al, 2008) and in ewes (Hall et al, 1994; Gonzalez et al, 1997; Gaskins et al, 2005; Aliyari et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…However, GDF9 is another major gene that is responsible for the highly prolific phenotype in sheep. It has a major role in growth and differentiation of antral follicles in female reproduction in mammals (Chu et al, 2011a). A mutation (FecG H ) in GDF9 gene in heterozygous form was seen to be responsible for a high ovulation rate, but in homozygous form it causes infertility in Cambridge and Belclare sheep (Hanrahan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Among these candidate genes, the GDF9 (growth and differentiation factor 9) gene which belongs to transforming growth factor β superfamily (TGFβ) and mapped on ECA14 plays crucial roles in determining follicle growth and controlling the ovulation rate (Hanrahan et al, ; Paulini & Melo, ). In addition, several studies have confirmed the involvement of genetic variants of GDF9 in women with dizygotic twins (Montgomery et al, ; Palmer et al, ) and with litter size in domesticated animals including sheep (El Fiky, Hassan, & Nassar, ; Hanrahan et al, ; Nicol et al, ), pig (Zhang, Du, Chen, Yang, & Zhang, ), goat (Chu et al, ; Feng et al, ) and cattle (Tang, Yang, Li, & Yang, ).…”
Section: Discussionmentioning
confidence: 91%